Forecasting Analysis for Production Planning - Bobi Krisman Berkat Gulo; Serniati Zebua; Aferiaman Telaumbanua (International Journal of Economics Development Research (IJEDR), 2024)
The furniture industry plays a pivotal role in the economy by contributing to employment and meeting household needs. Effective production planning and forecasting are crucial for furniture manufacturers to navigate market uncertainties and optimize resource utilization. This study focuses on "Forecasting Analysis and Production Planning for Furniture at UD. Bersaudara, Gido District, Nias Regency," aiming to address production challenges related to demand variability and raw material management. Using a quantitative descriptive approach, data was collected through observation, unstructured interviews, and documentation at UD. Bersaudara. Sales forecasting was conducted using the Moving Average method, demonstrating its effectiveness in estimating future furniture sales. The results highlight the importance of accurate forecasting in mitigating production inefficiencies and ensuring optimal inventory management. Key findings underscore the significance of integrating information systems, staying attuned to market trends, and providing training for personnel involved in forecasting and production planning. By adopting suitable forecasting methodologies and enhancing operational strategies, UD. Bersaudara can enhance production efficiency, minimize inventory risks, and bolster competitiveness in the furniture market.